Biomimetic electrospun nanofibrous scaffold for tissue engineering: preparation, optimization by design of experiments (DOE), in-vitro and in-vivo characterization - Anjum, Shabnam; Li, Ting; Arya, Dilip Kumar; Ali, Daoud; Alarifi, Saud; Yulin, Wang; Hengtong, Zhang; Rajinikanth, P. S.; Ao, Qiang (Frontiers in Bioengineering and Biotechnology, 2023)
Electrospinning is a versatile method for fabrication of précised nanofibrous materials for various biomedical application including tissue engineering and drug delivery. This research is aimed to fabricate the PVP/PVA nanofiber scaffold by novel electrospinning technique and to investigate the impact of process parameters (flow rate, voltage and distance) and polymer concentration/solvent combinations influence on properties of electrospun nanofibers. The in-vitro and in-vivo degradation studies were performed to evaluate the potential of electrospun PVP/PVA as a tissue engineering scaffold. The solvents used for electrospinning of PVP/PVA nanofibers were ethanol and 90% acetic acid, optimized with central composite design via Design Expert software. NF-2 and NF-35 were selected as optimised nanofiber formulation in acetic acid and ethanol, and their characterization showed diameter of 150–400 nm, tensile strength of 18.3 and 13.1 MPa, respectively. XRD data revealed the amorphous nature, and exhibited hydrophilicity (contact angles: 67.89° and 58.31° for NF-2 and NF-35). Swelling and in-vitro degradability studies displayed extended water retention as well as delayed degradation. FTIR analysis confirmed solvent-independent interactions. Additionally, hemolysis and in-vitro cytotoxicity studies revealed the non-toxic nature of fabricated scaffolds on RBCs and L929 fibroblast cells. Subcutaneous rat implantation assessed tissue response, month-long biodegradation, and biocompatibility through histological analysis of surrounding tissue. Due to its excellent biocompatibility, this porous PVP/PVA nanofiber has great potential for biomedical applications.